Changing Protagonists: Managing Economic Activities in Late Antique Lusitania - Carneiro, André (Gerión. Revista de Historia Antigua, 2021)
The Roman province of Lusitania went through a sequence of processes from the end of the 4th century onwards that resulted in the end of the classical landscape. The Christian Church gradually replaced private entrepreneurship in the management of the main economic activities and the organization of the daily activities. This process is difficult to characterize, but some archaeological evidence, from specific sites and from the analysis of the rural settlement patterns, emerges. Some considerations will be presented here, trying to contextualize certain mechanisms of change.
Keywords: Settlement Patterns; Villa; Rural Economy; Agriculture